Computing Value of Production (VoP) for the Ag-Incentives NRA Dataset - Laborde Debucquet, David; Mamun, Abdullah (International Food Policy Research Institute, 2023)
This document describes the steps involved in generating the value of production in the Ag-Incentives database.